Optimization of heterogeneous Catalyst-assisted fatty acid methyl esters biodiesel production from Soybean oil with different Machine learning methods - Walid, K. A.; Saud, M.A.; Shereen, H.E.; Tazeddinova, D.; Samif, G.; Bassem F., F.; Mohammed, Z.; Mohammed, A.; Chia-Hung, S.; Hoang, C. N.; Omark, M. (Arabian Journal of Chemistry., 2022)
There is a growing attention to the bio and renewable energies due to fast depletion of fossil fuels as well as the global warming problem. Here, we developed a modeling and simulation method by means of artificial intelligence (AI) for prediction of the bioenergy production from vegetable bean oil. AI methods are well known for prediction of complex and nonlinear process. Three distinct Adaptive Boosted models including Huber regression, LASSO, and Support Vector Regression (SVR) as well as artificial neural network (ANN) were applied in this study to predict actual yield of Fatty acid methyl esters (FAME) production. All boosted utilizing the Adaptive boosting algorithm. The important influencing parameters on the biodiesel production such as the catalyst loading (CAO/Ag, wt%) and methanol to oil (Soybean oil) molar ratio were selected as the input variables of models while the yield of FAME production was selected as output. Model hyper-parameters were tuned to maintain generality while improving prediction accuracy. The models were evaluated using three distinct metrics Mean Absolute Error (MAE), Root Mean Square Error (RMSE), and R2. Error rates of 8.16780E-01, 4.43895E-01, 2.06692E + 00, and 3.92713 E-01 were obtained with the MAE metric for boosted Huber, SVR, LASSO and ANN models. On the other hand, the RMSE error of these models were about 1.092E-02, 1.015E-02, 2.669E-02, and 1.01174E-02, respectively. Finally, the R-square score were calculated for boosted Huber, boosted SVR, and boosted LASSO as 0.976, 0.990, 0.872, and 0.99702, respectively. Therefore, it can be concluded that although the boosted SVR and ANN models were better models for prediction of process efficiency in terms of error, but all algorithms had high accuracy. The optimum yield of 83.77% and 81.60% for biodiesel production were observed at optimum operating values from boosted SVR and ANN models, respectively. Растет внимание к био и возобновляемым источникам энергии из-за быстрого истощения запасов ископаемого топлива, а также проблемы глобального потепления. Здесь мы разработали метод моделирования и симуляции с помощью искусственного интеллекта (ИИ) для прогнозирования производства биоэнергии из растительного масла. Методы ИИ хорошо известны для предсказания сложных и нелинейных процессов. В этом исследовании для прогнозирования фактического выхода продукции метиловых эфиров жирных кислот (МЭЖК) применялись три различные модели Adaptive Boosted, в том числе регрессия Хубера, LASSO и регрессия опорных векторов (SVR), а также искусственная нейронная сеть (ANN). Все усилено с использованием алгоритма Adaptive boosting. В качестве входных переменных моделей были выбраны важные параметры, влияющие на производство биодизеля, такие как загрузка катализатора (CAO/Ag, мас.%) и молярное отношение метанола к маслу (соевое масло), а выход продукции МЭЖК был выбран в качестве выходных данных. Гиперпараметры модели были настроены для сохранения общности при одновременном повышении точности прогноза. Модели оценивались с использованием трех различных показателей: средней абсолютной ошибки (MAE), среднеквадратической ошибки (RMSE) и R2. Коэффициенты ошибок 8,16780E-01, 4,43895E-01, 2,06692E + 00 и 3,92713 E-01 были получены с помощью метрики MAE для моделей Huber, SVR, LASSO и ANN с усилением. С другой стороны, среднеквадратическая ошибка этих моделей составляла около 1,092E-02, 1,015E-02, 2,669E-02 и 1,01174E-02 соответственно. Наконец, был рассчитан показатель R-квадрата для усиленного Huber, усиленного SVR и усиленного LASSO как 0,976, 0,990, 0,872 и 0,99702 соответственно. Таким образом, можно сделать вывод, что, хотя форсированные модели SVR и ANN были лучшими моделями для прогнозирования эффективности процесса с точки зрения ошибки, все алгоритмы имели высокую точность. Оптимальный выход 83,77% и 81,60% для производства биодизельного топлива наблюдался при оптимальных рабочих значениях моделей с форсированным SVR и ANN соответственно.
Keywords: импакт-фактор 2022; скопус; зарубежное издание; дальнее зарубежье; научный журнал; периодическое издание; зарубежные авторы; возобновляемые источники энергии; биотопливо; биогаз; биодизельное топливо